Characterizing the Zeeman slowing force for 40Ca19F molecules. (8th September 2021) - Kaebert, P; Stepanova, M; Poll, T; Petzold, M; Xu, S; Siercke, M; Ospelkaus, S
Abstract: In this paper we investigate the feasibility of Zeeman slowing calcium monofluoride molecules originating from a cryogenic buffer gas cell. We measure the A 2 Π 1 / 2 ( v = 0, J = 1 2 ) − X 2 Σ 1 / 2 ( v = 0, N = 1 ) hyperfine spectrum of CaF in the Paschen–Back regime and find excellent agreement with theory. We then investigate the scattering rate of the molecules in a molecular Zeeman slower by illuminating them with light from a 10 mW broad repumper and a 10 mW multi-frequency slowing laser. By comparing our results to theory we can calculate the photon scattering rate at higher powers, leading to a force profile for Zeeman slowing. We show results from a simple 1D simulation demonstrating that this force is narrow enough in velocity space to lead to significant velocity compression, and slowing of the molecules to trappable velocities.